One Step Synthesis and Photocatalytic Activity of Rare Earths/Rutile TiO2 - Bian, Liang; Song, Mianxin; Zhou, Tianliang; Xu, Jinbao; Wang, Lei (Asian Journal of Chemistry, 2012)
Rutile TiO2 and 12 rare earths (RE)/rutile TiO2 were synthesized by one-step method at 80 ºC. Subsequently, they were characterized using XRD, SEM, particle size, DRS and Zeta (z) potential. The results indicated that the rare earth/rutile TiO2 was successfully synthesized at 80 ºC and rare earth obviously improved the parameters of photocatalytic activity of rare earth/rutile TiO2, such as crystalline lattice diameters, particle size, band gap and z potential.